2020
DOI: 10.1017/s071498082000015x
|View full text |Cite
|
Sign up to set email alerts
|

Whole Person, Whole Journey: Developing a Person-Centred Regional Dementia Strategy

Abstract: ABSTRACT We present the development of a regional dementia strategy in Southwestern Ontario, Canada. We worked with stakeholders in a regional health authority to develop a dementia strategy. We conducted interviews with persons with dementia and their care partners (n = 26) and health care administrators and policy makers (n = 33); and administered a priority-setting survey (n = 64). Both parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The remaining fourteen studies [ 6 , 31 43 ] included various professions without differentiating between them. Most of these references also included physicians [ 6 , 33 35 , 37 , 39 , 40 , 43 ] and various nurses [ 6 , 31 , 32 , 34 , 35 , 37 39 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The remaining fourteen studies [ 6 , 31 43 ] included various professions without differentiating between them. Most of these references also included physicians [ 6 , 33 35 , 37 , 39 , 40 , 43 ] and various nurses [ 6 , 31 , 32 , 34 , 35 , 37 39 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies did not refer to a theoretical framework [ 6 , 16 20 , 22 – 35 , 37 39 , 41 , 43 ]. Only four studies [ 21 , 36 , 40 , 42 ] reported to have used a theoretical framework. Haralambous et al [ 36 ] used the Cultural Exchange Model.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations